The death of author Veronica Stigger - Da Rosa, Victor Luiz [UNESP] (FapUNIFESP (SciELO), 2019)
This article analyzes Veronica Stigger's fictional writing - especially the short story “200m2”. In this short story Verônica (the character) stages her own suicide, thus enacting the death of the author, suggesting a poetics within Stigger’s literature. One of the theoretical consequences of the scene of the author’s death leads us to examine the tension between the “dead letter” and the living word, according to Jacques Rancière’s re-reading of Plato's critiques on writing. But this scene also points towards a critical alternative in Stigger’s literature against spectacle society as it establishes a series of “separations” between writing and its object. Finally this line of investigation opens up an unavoidable question about the analyzed short story - a question that must also be applied to the author's subsequent books, and yet does not seem to offer any acceptable answer: if the has author died, how is she able to keep writing?
A morte da autora Veronica Stigger
Keywords: Authorship; Dead letter; Spectacle; Veronica Stigger